Human movements: immigrants and asylum seekers. Two sides of the same coin - Iuliana Mihai; Isabel Novo-Corti (The Central European Review of Economics and Management (CEREM), 2019)
Aim: Millions of people are displaced globally, as refugees, asylum seekers or migrants. Although, at a first glance, crisis and conflicts are considered the main trigger for these movements, the migration challenge may have different roots: demographic trends, poverty, the globalization of communication, etc. The present article is an introduction to the main concepts and terminology regarding migration and it links the migration with actual labor problems within the EU.Design: The article shows how migration terminology is reflected in the EU migration policy and how migration policy affects labor policy and vice versa. The article is to be considered a state of the art or methanalysis and explains the concepts: in-migration, out-migration, refugees, asylum-seekers. In addition, it draws attention to controversies regarding the use of concepts: illegal migration, irregular migration and return migration.Conclusions: The article presents eight main economic theories of migration. Five of them have as subject of analysis the determinants of migration and the other three have the subject of analysis the perpetuation of migration. Some of the main theories analyzed here are the neoclassical theory of migration, the human capital theory of migration, the new economics theory of migration, world system theory, network theory, migration systems theory.Originality: The article demonstrates the fact that neither of these economic theories/models explain adequately the actual determinants of migration and it proposes a new model focused more on the transdisciplinary effects of human movements.
Keywords: JO15; J61; J15; 330; migration; crisis; development; asylum seekers; labor market policies